ISOLATION OF Lactobacillus plantarum LPBM10 AND PARTIAL CHARACTERIZATION OF ITS BACTERIOCIN - ZAPATA, Sandra; MUÑOZ, Juliana; RUIZ, Orlando S.; MONTOYA, Olga I.; GUTIÉEREZ, Pablo A. (Vitae, 2009)
Lactic acid bacteria are a group of Gram-positive microorganisms widely used in food preservation due to their probiotic properties and their ability to produce bacteriocins. Bacteriocins are antibiotic compounds of peptide nature which have been studied intensively for their potential use as substitutes of chemical additives in food preservation. In this paper we report the isolation and characterization of Lactobacillus plantarum LPBM10. This bacteriocin was isolated from fermented milk and can be classified as probiotic. The free cell extract was active against Gram positive and Gram negative bacteria. This bacteriocin is highly thermostable, active at low pH and its activity is not affected by proteinase K, chelating agents and detergents. This antibiotic compound was purified by dyalisis and size exclusion chromatography. Its analysis by UV and FT-IR spectroscopy suggests that bacteriocin is a peptide containing some cystein and tyrosine aminoacids. Experiments on dyalized crude extract by ion-exchange chromatography suggest the presence of an anionic inhibitor of LPBM10.